An uncharted territory of sexualized drug use: exploring the dynamics of chemsex among young and adolescent MSM including self-identified gay men in urban Dhaka, Bangladesh - Irfan, Samira Dishti; Sarwar, Golam; Emran, Junyed; Khan, Sharful Islam (Frontiers in Psychology, 2023)
Global and local literature depicted the pervasiveness of chemsex among men who have sex with men, yet there is limited evidence on adolescents and youth. Though literature showed their engagement in chemsex, further exploration is warranted about their socio-sexual contexts and implications. Therefore, this article explored the contexts and implications of chemsex on young and adolescent MSM. This article is extracted from qualitative research evidence, and research data are triangulated by programmatic evidence on adolescent and young MSM from two ongoing pilot interventions. The key motivational factors for engaging in chemsex were primarily rooted in the dynamics of their peer networks. Specifically, the onset of drug use is predominantly attributed to curiosity towards experimentation with methamphetamine, peer influence, propensity to lose weight, and increasing courage to approach potential sexual partners. Moreover, they continued taking drugs as it enhanced their sexual performance, thus perpetuating chemsex. Additionally, the findings revealed several sexual implications of methamphetamine, e.g. bolstering their sexual “stamina”, increasing their propensity towards sexual violence, and reducing their decision-making abilities and judgment, thus collectively decreasing condom use. In essence, chemsex is considerably driven by their socio-sexual contexts, thus perpetuating sexual risk behaviors and compromising sexual health outcomes. Therefore, harm reduction interventions targeted need to be designed keeping in mind their socio-sexual dynamics and age.